(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
This article aims to analyze the impact of clearance of funds measured by the ratio between debt and equity in the development of best practices Corporate Social Responsibility (CSR) of the SMEs in Zone 7 comprising the provinces Ecuador Loja, Zamora and El Oro. In this paper we analyze if the excess resources of the company allows it to generate CSR practices. It has generated an indicator that measures the CSR of SMEs through the ETHOS indicators applied to a sample of 124 companies and has also been used indicator of financial slack. Through regression analysis the impact of resource slack is analyzed from approaches equity - debt ratio and CSR. The results obtained in this investigation to prove that the financial clearance approach debt - equity has an impact on the good practices of CSR. So it could be concluded that SMEs in the Region 7 Ecuador interested in strengthening its CSR practices should focus their efforts to generate a surplus of resources from the perspective of the debt ratio - equity.